Ant functional groups and their effects on other insects in organic and conventional cropping areas - Milene Andrade Estrada; Joabe Rodrigues Pereira; Ângela Alves de Almeida; André Barbosa Vargas; Fábio Souto Almeida (EntomoBrasilis, 2023)
The present research aimed to study the functional groups of ants in organic and conventional cropping areas and assess their influence on the abundance of other insects in agroecosystems. Sampling was carried out in eight rural properties with organic, and eight with conventional crops in Paraíba do Sul, state of Rio de Janeiro, Brazil. Fifteen pitfall soil traps were installed to collect ants in each property, in April and May 2016. The ants collected were dry-mounted and identified. The insect abundances of the orders Coleoptera, Hemiptera, and Orthoptera were also obtained. Ants were classified into seven functional groups. The functional group with the largest number of species was “omnivores that inhabit the soil and the leaf litter,” followed by “omnivores that inhabit the soil, the leaf litter, and the plants.” The group “omnivores that inhabit the soil and the leaf litter” showed the highest abundance of ants in both types of crops. The mean richness of functional groups was significantly higher in organic than in conventional crops. We only observed the effect of the abundance of ants of the group “omnivores that inhabit the soil, the leaf litter, and the plants” on the abundance of coleopterans in conventional crops. Hence, areas with organic crops are more favorable for maintaining an ant fauna with higher functional diversity than areas using the conventional cropping system.